Development of PES-based hydrophilic membranes via corona air plasma for highly effective water purification. Issue 3 (June 2022) - Salimi, Parisa; Aroujalian, Abdolreza; Iranshahi, Davood
Abstract: An ecological and practical approach based on the corona-induced graft copolymerization technique was applied to modify the surface properties of the polyethersulfone (PES) membrane using SBMA zwitterionic monomers to improve the anti-fouling ability during the process of separating oil-water emulsions. As a result, the effects of corona treatment conditions on the physicochemical properties of the membrane were characterized using different analytical instruments. The surface hydrophilicity of the PES membrane was considerably improved, characterized by a decrease in CA from 72 to ∼17◦. In addition, the highest pure water and emulsion fluxes of the PES-g-SBMA membrane were improved by 1247% and 325% compared to the unmodified membrane, reaching 840 Lm −2 .h −1 and 364 Lm −2 .h −1, respectively. The modified membranes exhibited not only high flux but also high oil rejection (> 99%), showing promising potential for use in industrial applications due to the production of high-quality water with a concentration of oil less than six ppm. Overall, this study provides an easy one-step preparation method for PES graft membranes with high anti-fouling property whose thickness and morphology can only be fully controlled by changing the corona parameters (power and time) without the need for a chemical initiator or the use of more monomer. Graphical Abstract: ga1 Highlights: PES membrane surface modification was done via green, rapid and low-cost operation corona-induced graft copolymerization. The results showed that the structure and thickness of the grafted layer are affected by corona exposure time and power. The different corona conditions were evaluated to obtain the maximum flux and flux recovery ratio (FRR). The modified membranes demonstrate high water permeability of oily wastewater with excellent recyclability.